Dynamic modeling of AP1000 steam generator for control system design and simulation. (November 2017) - Wan, Jiashuang; Wu, Shifa; Nuerlan, Areai; Zhao, Fuyu
Highlights: A lumped parameter dynamic model for AP1000 U-tube steam generator is developed. Six types of typical operational transients are simulated by both the linear and nonlinear models. Results show that the nonlinear and linear models show a good agreement in terms of the changing trends. Abstract: A lumped parameter dynamic model for AP1000 U-tube steam generator (UTSG) is developed based upon the fundamental conservation of fluid mass, energy, and momentum. The steam generator model consists of 15 lumps with the effective secondary heat exchange region divided into a subcooled heat transfer region and a boiling heat transfer region with a dynamic boundary. Moreover, a linear Takagi-Sugeno (TS) model for the steam generator is also proposed using multiple model approach, composed of several locally accurate linear models. The linear TS model can describe the global nonlinear steam generator system with some degree accuracy. In MATLAB/Simulink environment, six types of typical operational transients are simulated by both the linear and nonlinear models using the results obtained from the CENTS as the inputs to the proposed models. Under the same model inputs, the comparison of simulation results obtained by proposed models and CENTS shows a good agreement in terms of the changing trends. In addition, the results also demonstrate that the TS model not only has a satisfactory precision but also at least a five times faster running speed than the nonlinear model, which makes it easy to be applied to the design and optimization of feedwater control system.